Homicide and Suicide During the Perinatal Period: Findings from the National Violent Death Reporting System - Palladino, Christie Lancaster (2011)
OBJECTIVE: Homicide and suicide are two important and potentially preventable causes of maternal injury. We analyzed data from the National Violent Death Reporting System to estimate the rates of pregnancy-associated homicide and suicide in a multi-state sample, to compare these rates with other causes of maternal mortality, and to describe victims’ demographic characteristics. METHODS: We analyzed data from female victims of reproductive age from 2003–2007. We identified pregnancy-associated violent deaths as deaths due to homicide or suicide during pregnancy or within the first year postpartum. We calculated the rates of pregnancy-associated homicide and suicide as the number of deaths per 100,000 live births in the sample population. We used descriptive statistics to report victims’ demographic characteristics and prevalence of intimate partner violence (IPV). RESULTS: There were 94 counts of pregnancy-associated suicide and 139 counts of pregnancy-associated homicide, yielding pregnancy-associated suicide and homicide rates of 2.0 and 2.9 deaths/100,000 live births, respectively. Victims of pregnancy-associated suicide were significantly more likely to be older and of Caucasian or American Indian descent as compared to all live births in NVDRS states. Pregnancy-associated homicide victims were significantly more likely to be at the extremes of the age range and African American. 54.3% of pregnancy-associated suicides involved intimate partner conflict that appeared to contribute to the suicide. 45.3% of pregnancy-associated homicides were IPV-associated. CONCLUSIONS: Our results indicate that pregnancy-associated homicide and suicide are important contributors to maternal mortality and confirm the need to evaluate the relationships between socio demographic disparities and IPV with pregnancy-associated violent death.